Accumulation of mitochondrial DNA with a point mutation in tRNALeu(UUR) gene induces brain dysfunction in mice - Kaori Ishikawa; Daiki Miyata; Satoko Hattori; Haruna Tani; Takayoshi Kuriyama; Fan-Yan Wei; Tsuyoshi Miyakawa; Kazuto Nakada (Elsevier, 2024)
Brain functions are mediated via the complex interplay between several complex factors, and hence, identifying the underlying cause of an abnormality within a certain brain region can be challenging. In mitochondrial disease, abnormalities in brain function are thought to be attributed to accumulation of mitochondrial DNA (mtDNA) with pathogenic mutations; however, only few previous studies have directly demonstrated that accumulation of mutant mtDNA induced abnormalities in brain function. Herein, we examined the effects of mtDNA mutations on brain function via behavioral analyses using a mouse model with an A2748G point mutation in mtDNA tRNALeu(UUR). Our results revealed that mice with a high percentage of mutant mtDNA showed a characteristic trend toward reduced prepulse inhibition and memory-dependent test performance, similar to that observed in psychiatric disorders, such as schizophrenia; however, muscle strength and motor coordination were not markedly affected. Upon examining the hippocampus and frontal lobes of the brain, mitochondrial morphology was abnormal, and the brain weight was slightly reduced. These results indicate that the predominant accumulation of a point mutation in the tRNALeu(UUR) gene may affect brain functions, particularly the coordination of sensory and motor functions and memory processes. These abnormalities probably caused by both direct effects of accumulation of the mutant mtDNA in neuronal cells and indirect effects via changes of systemic extracellular environments. Overall, these findings will lead to a better understanding of the pathogenic mechanism underlying this complex disease and facilitate the development of optimal treatment methods.